A new endemic genus of Oecleini from Seychelles (Hemiptera: Fulgoromorpha: Cixiidae) - Holzinger, Werner E. (Zootaxa, 2009)
A new genus, Fipsianus gen. nov., from Seychelles is described. It is closely related to the genera Volcanalia, Eumyndus, Borbonomyndus and Nesomyndus. Fipsianus, is endemic to the granitic “inner islands” and comprises two species, Fipsianus picturatus (Distant , 1917) comb. nov. (type species; synonym Volcanalia varicolor Distant, 1917, syn. nov.) on Mahé and Silhouette islands and Fipsianus andreae sp. nov. on Praslin island. Both species are monophagous on the thief palm Phoenicophorium borsigianum.